Risk factors for relapse in non-infectious cryoglobulinemic vasculitis, including type I cryoglobulinemia: a systematic review - Rajendran, Nithya; Rameli, Puteri Maisarah; Awad, Hanaa (Frontiers in Immunology, 2023)
Background: Data on Non-Infectious Cryoglobulinemic Vasculitis (NICV) is scarce, especially concerning the management of relapses which are troublesome. We aimed to investigate risk factors for relapse in NICV. Methods: A systematic literature search of CINAHL, EMBASE, MEDLINE, Scopus and Web of Science databases were implemented until April 2023. Eligible studies included randomised control trials, observational studies and case series with ≥4 patients. Two reviewers independently extracted data and assessed the quality of the eligible studies. Results: A total of 3724 articles were retrieved from a database search, with 27 studies meeting the inclusion criteria for review. Most studies (n=23) detailed relapses, with time to relapse varying between 1 - 80 months. The relapse rate was reported at 28% in Type I NICV and ranged from 22% to 60% in mixed NICV. Risk factors for relapse in NICV were identified based on the cryoglobulin subtype and correlated with clinical and immunological responses to varying treatment regimens. Type I NICV with associated lymphoproliferative disorder exhibited a response-relapse pattern. Cutaneous and articular involvement, and incomplete clinical and immunological responses to treatment, particularly Corticosteroid monotherapy, and occasionally with Rituximab, influenced the risk of relapse in Type II and Type III NICV. Conclusion: Our findings underscore the significance of attaining both clinical and immunological responses and identifying risk factors for relapse in NICV. Appropriate risk stratification of NICV patients is essential for the successful implementation of effective treatment strategies.